The Effect of Substitution on the Dyeing and Spectroscopic Properties of Some Monoazo Disperse Dyes (Biological Sciences - PJSIR, 2006)
A range of monoazo disperse dyes has been synthesized. The colour, dyeing and fastness properties of the dyes on polyester, nylon and secondary acetate fibre at 1/1 standard depth have been examined and rationalized in terms of dye structure. The visible absorption behaviour of the dyes was also investigated. In general, substitutions on the diazo component have a significant effect on the visible absorption maxima of the dyes. Increasing the solvent polarity also had a pronounced effect on the absorption maxima.